PARTISIPASI WARGA UNTUK PENYEBARAN INFORMASI PADA INSTAGRAM @ASLISEMARANG SEBAGAI JURNALISME WARGA - Nabila Putri Haryanto; Swita Amallia Hapsari (Universitas Tidar, 2025)
Social media has become a platform for people to get information and news. This happens because social media is able to make people participate in disseminating information. Information dissemination occurs actively on social media, the community can participate in disseminating information. Citizen journalism as a new form of journalism is a breath of fresh air for the presentation of information. This research uses a qualitative method with a descriptive approach. The theory used in this research is the theory of citizen participation expressed by Sunganh & Chung. The purpose of this research is to find out how the dissemination of citizen journalism information that occurs on the Instagram account @aslisemarang. This research uses primary data sources obtained through interviews with sources and observations on the @aslisemarang Instagram account. While secondary data sources are obtained through observation of literature, books, and journals. The results of this study indicate that the Instagram account @aslisemarang as an account for disseminating citizen journalism information occurs in accordance with the ethics of citizen participation proposed by Sungahn & Chung.